The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1098/rspb.2019.0834
|View full text |Cite
|
Sign up to set email alerts
|

Under the radar: long-term perspectives on ecological changes in lakes

Abstract: Aquatic ecosystems are constantly changing due to natural and anthropogenic stressors. When dealing with such ‘moving targets’, one of the greatest challenges faced by scientists, managers and policy makers is to use appropriate time scales for environmental assessments. However, most aquatic systems lack monitoring data, and if a programme does exist, rarely have data been collected for more than a few years. Hence, it is often difficult or impossible to determine the nature and timing of ecosystem changes ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 63 publications
2
56
0
Order By: Relevance
“…Respondent groups include both obligate oxygenic photoautotrophs (in particular Chlorophyceae and Prymnesiophyceae) and mixotrophs (in particular Dinophyceae). Our combined DNA and pigment-based results obtained for 48 lakes are in line with several paleolimnological studies that have reported an increase in primary production throughout the Holocene 10,11 . The ratio and rates of autotrophic and heterotrophic production constitute the basis of the metabolic balance of lake ecosystems in the form of primary productivity and respiration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Respondent groups include both obligate oxygenic photoautotrophs (in particular Chlorophyceae and Prymnesiophyceae) and mixotrophs (in particular Dinophyceae). Our combined DNA and pigment-based results obtained for 48 lakes are in line with several paleolimnological studies that have reported an increase in primary production throughout the Holocene 10,11 . The ratio and rates of autotrophic and heterotrophic production constitute the basis of the metabolic balance of lake ecosystems in the form of primary productivity and respiration.…”
Section: Discussionsupporting
confidence: 90%
“…The second part of the twentieth century is unambiguously a time of major and multiple threats that might have disproportionately affected lake biodiversity and associated ecological functions (e.g., nutrient recycling, efficiency of trophic transfer, and quality of fish production) 3 , 8 . Paleolimnological studies have provided evidence supporting the occurrence of states of change in lake ecosystems, for instance the accelerated hypoxia in European lakes after 1900 9 or the increase in autochthonous primary production in lakes (e.g., Lake Superior 10 and see review by Smol 11 ). However, much less is known about the long-term changes of biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the majority of ecosystems worldwide, including freshwater ecosystems, are threatened by multiple anthropogenic stressors (Vörösmarty et al ., 2010; McCluney et al ., 2014; Albert et al ., 2020; Birk et al ., 2020). Lakes are no exception, as they are threatened, inter alia , by climate change, land‐use intensification, eutrophication, acidification, water abstraction, water‐level regulation, morphological alteration, and invasive species (Dudgeon et al ., 2006; Smol, 2019). Understanding the resilience and recovery of lakes to environmental change has thus emerged as an important research program from the perspectives of biodiversity conservation and ecosystem services (Angeler & Drakare, 2013; Angeler et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic activities such as changes in land-use can induce major transformations in lake systems via increased catchment erosion, and its effect on sedimentation rates and nutrient loads leading to eutrophication and ecological shifts affecting lake biota [1][2][3][4][5]. Tracing such environmental dynamics over short timescales and assessing the type and timing of the main drivers of change are needed for a better understanding of the complex cause-effect relationship between environmental responses, anthropogenic activities and natural climate variability, and therefore to improve management strategies [6][7][8].…”
Section: Introductionmentioning
confidence: 99%